Pemahaman Masyarakat Kabupaten Barru terhadap Hukum Waris Islam dan Penerapannya: Perspektif Mazhab al-Syafi’i dan Hanafi - Wahyuni, Pritha; Bakry, Muammar; Mustari, Abdillah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The law regarding the division of inheritance has been regulated in Islamic law, but the entire community has not understood the understanding of the concept of inheritance distribution in Islam. The main problem in this study is how the understanding of the Atapangnge community, Tanete Rilau District, Barru Regency about Islamic inheritance law and its application in the perspective of the Syafi’i and Hanafi Schools. The purpose of this study is to determine the understanding of the Atapangnge community, Tanete Rilau District, Barru Regency about Islamic inheritance law and its application in the perspective of the Syafi’i and Hanafi Schools. The purpose of this study is to find out how the understanding and application of Islamic inheritance law in society according to the perspective of the al-Shafiyah and Hanafi Schools. The research method used is qualitative field research with a legal and normative sociology research approach. In collecting data, the authors used literature studies and 8-field studies. The techniques that the author uses are observation, interviews, and documentation. The data obtained is then processed and analyzed through three stages, namely: data reduction (data selection), data presentation, and conclusion. The results of this study show that the community has not understood and applied Islamic inheritance law, which applied to the Atapangnge community, namely customary law inheritance so that conflicts do not occur. It is clear that urf among the Imams of the School have the same view that can be used as a legal argument, Imam Syafi’i after living in Egypt changed some of his legal fatwas that had been issued before, because the customs of each region were different, as well as Imam Hanafi in his legal decisions cannot be separated from the conditions and situations that affect him.